A Fuzzy Logic Enhanced Environmental Protection Education Model for Policies Decision Support in Green Community Development - Sung-Lin Hsueh (The Scientific World Journal)
This study proposes the promotion of environmental protection education among communities as a solution to the serious problems of high energy consumption and carbon emissions around the world. Environmental protection education has direct and lasting influences on everyone in society; therefore, it is helpful in our fight against many serious problems caused by high energy consumption. In this study, the Delphi method and the fuzzy logic theory are used to develop a quantizing assessment model based on qualitative analysis. This model can be used to assess the results and influences of community residents’ participation in environmental protection education on green community development. In addition, it can be used to provide references for governing authorities in their decision making of green community development policies.